‎ Sustainable Asphalt Mixtures : a Scientific Metric Analysis and ‎Bibliometrics Review ‎ (Journal of University of Babylon for Engineering Sciences, 2024)
The environmental effects of building a new road are numerous and include significant material and energy use. Additionally, there has been a notable increase in the price of crude oil, the primary source of bituminous binder, in recent years (most notably in 2001–2008). The cost of asphalt mixtures as a whole has gone up as a result. Measures with strong sustainability credentials must be extensively implemented in order to fight price increases and encourage sustainable activities. The asphalt pavement business may become more sustainable and cost-efficient by creating new materials and technologies that include trash, recycled resources, and greener components into the asphalt mixture production cycle. Sustainable asphalt mixtures demonstrate improved durability and longer service life, reducing the need for frequent maintenance and rehabilitation. This leads to cost savings and reduced disruption to traffic. The purpose of this study is to determine which nations and institutions have published the greatest number of articles on the topic of sustainable asphalt mixtures, as well as to identify and aggregate the most noteworthy research papers using "Dimensions" and analyze the data using the VOS viewer software.  Additionally, it was done to find out more about the writers' collaboration